Asymptomatic infection in family contacts of patients with human visceral leishmaniasis in Três Lagoas, Mato Grosso do Sul State, Brazil Infecção assintomática em contactantes de pacientes com leishmaniose visceral humana em Três Lagoas, Mato Grosso do Sul, Brasil - Ana Lúcia Lyrio de Oliveira; Anamaria Mello Miranda Paniago; Marcos Antônio Sanches; Maria Elizabeth Cavalheiros Dorval; Elisa Teruya Oshiro; Cássia Rejane Brito Leal; Fernando Henrique de Paula; Luís Gustavo Pereira; Rivaldo Venâncio da Cunha; Márcio Neves Bóia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The Brazilian city of Três Lagoas, Mato Grosso do Sul State, has experienced an urban outbreak of visceral leishmaniasis since 2000. In 2002, due to the increase in the number of cases, 46 families with cases of visceral leishmaniasis were studied to verify the prevalence of asymptomatic infection in household contacts. Indirect immunofluorescence and ELISA showed a 36.4% positive infection rate. There were no cases of symptomatic disease among these contacts. There was no statistically significant difference in gender or age. Median age was 21 years, and the 10-19-year age bracket was the most heavily affected (23%). As for family characteristics, no differences were observed in schooling or family income; most families (58.7%) owned their homes, which were built of masonry (97.8%) and had adequate infrastructure. All the families reported what were probably phlebotomine sand flies in the peridomicile. In conclusion, asymptomatic visceral leishmaniasis infection is frequent and occurs in both males and females, regardless of age. O Município de Três Lagoas, Mato Grosso do Sul, Brasil, foi alvo de uma epidemia de leishmaniose visceral a partir de 2000. Em 2002, devido ao incremento de casos, estudou-se 46 famílias que apresentavam um caso de doença para verificar-se o percentual de positividade de infecção assintomática por leishmaniose visceral em contactantes. Encontrou-se 36,4% de positividade pelos testes sorológicos Reação de Imunofluorescência Indireta e/ou imunoenzimático ELISA, sem diferença estatisticamente significativa quanto ao sexo e faixa etária. A mediana de idade foi de 21 anos, sendo a faixa etária mais acometida de 10 a 19 anos (23%). Quanto às características familiares não observaram-se diferenças quanto ao nível de instrução e renda familiar; a moradia, em sua maioria, era própria (58,7%), em alvenaria (97,8%), com infra-estrutura adequada. Todas as famílias relataram a presença de provável flebotomíneo no peridomicílio. Conclui-se que a infecção assintomática por leishmaniose visceral é freqüente, ocorrendo em homens e mulheres, independente de faixa etária.